Kebijakan Pengaturan Agraria Di Indonesia : Suatu Tinjauan Berdasarkan Undang-Undang Pokok Agraria (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
Before the existence of the Basic Agrarian Law Number 5 of 1960 concerning the Principles of Agrarian Law Formation, the dualism of rules governing land rights between Indonesians and non-Indonesians was the main catalyst for the formation of a state law that guarantees land rights within the State of Indonesia. This title was chosen so that I could research and inform the general public about Indonesia's agrarian law policies and practices. Because the studies obtained are based on references from books, articles, and regulations related to agrarian law or land politics, the methodology This research uses normative studies or literature studies. According to the research findings, the agrarian law policy developed in accordance with UUPA No. 5 of 1960 concerning the Principles of Agrarian Law is designed to lay the foundation for National Agrarian Law, which is a tool to realize prosperity, happiness, and justice for the State and the people, especially the peasantry, within the framework of a just and prosperous society. In addition, the policy is designed to lay the foundation for building unity and simplicity in the country.